Os números racionais aplicados na metrologia - INVENÇÃO, Ismael Felix (2019)
This paper tries to show an application of rational numbers in an area that some elementary or middle school students may want to work in the future - metrology - knowing some of their instruments, which are many used by workers who work in mechanics and civil construction, such as the graduated ruler, the trena, and the pachymeter, and that in these instruments one can see the use of rational numbers in the form of an improper and irreducible fraction, and not only in the form of integers which are more common in the daily life of the majority of people. For the practical application of the teaching of rational numbers, using instruments of metrology is applied in a class of elementary school in which the teacher has already explained about the rational numbers or is explaining, with the purpose of showing in practice, where and how rational numbers are used, in a more concrete way, with the materials in hand, also to stimulate the teacher to bring concrete materials to the classroom and that the student can manipulate it, to try to facilitate the student's learning. This practice occurred in a State School of Elementary Education located in the municipality of Barcarena / Pa with a group of the 8th year in two moments. At the first moment a kind of knowledge test was done, on the rational numbers through a test questionnaire with 5 questions and soon after delivering the test questionnaire, the part of the test was done on the whiteboard for all as form of revision and at the end was marked the second moment for the application of rational numbers with the use of metrology instruments. In the second moment the measuring instruments were presented to the students: the graduated ruler, the measuring tape and the caliper. Students were given the information contained in each instrument and how they should be used, focusing on the presence of rational numbers and also how these numbers are perceived and inserted in the daily life of those who work using these instruments more concretely using the equipment in question. hands of the students themselves, which most of them did not know. At the end they answered another test questionnaire, now using the instruments at hand, and that the results of the test questionnaires is recorded in this work, with a great satisfaction of learning and interest of the students.